Implementation of Future Early Childhood Education Curriculum that Meets the Aspirations of Today’s Parents - Yu Simin; Mohd Nazri Bin Abdul Rahman (Proceeding International Symposium on Global Education, Psychology, and Cultural Synergy, 2025)
In today's fast-changing society, parents’ expectations for early childhood education have broadened beyond academic achievement to include social responsibility, emotional regulation, creativity, and skills for future adaptation. As a vital foundation for children's growth, early education must evolve through curriculum innovation to meet these needs. This study explores how to design and implement curricula that align with modern parental expectations, drawing on the practical experiences of educators and researchers. The goal is to provide valuable insights for optimizing early childhood education to support children’s holistic development in a changing world.